IMPLEMENTASI PROGRAM KERJA KEPALA SEKOLAH TERHADAP KINERJA GURU DI MTS BABUSSALAM BESILAM PADANG TUALANG - Ahmad Ibnu Subhan; Ahmad Zaki; Pitriani Nasution (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
This research aims to find out first the planning of the principal's work programme on teacher performance at MTs Babussalam Besilam, second the principal's efforts to implement the principal's work programme on teacher performance at MTs Babussalam Besilam, third the obstacles to the implementation of the principal's work programme on teacher performance at MTs Babussalam Besilam. The method used in this research is qualitative by using data collection techniques in the form of observation, interviews, and documentation by focusing on information data sources, namely: Principal, vice principal, administration, and English teacher to strengthen the validity of the data obtained. From the results of this study using three findings, namely: First, the planning of the principal's work programme on teacher performance at MTs Babussalam Besilam has been carried out well, carried out in the form of meetings and deliberations with teachers, second, the principal's efforts to implement the principal's work programme on teacher performance at MTs Babussalam Besilam are carried out by giving assignments to teachers according to their abilities and work according to their expertise, third, the obstacles to the implementation of the principal's work programme on teacher performance at MTs Babussalam Besilam are carried out by teachers while working to find out the extent to which the improvement of teacher performance has been running.